IMPLIKASI PRESTASI BELAJAR EKONOMI DI PENGARUHI KONDISI SOSIAL ORANG TUA DAN MOTIVASI BELAJAR - Yorman Kasman (STKIP PGRI Tulungagung, 2022)
The focus of this research is to describe the impact that appears on the socio-economic conditions of families and learning motivation on the economic learning achievement of public high school students in the Bima district. This study is quantitative in nature, as it employs the regression analysis method to connect data points that demonstrate influence. The sampling model in this study employs a proportional random sampling technique, in which sample members are chosen at random and in proportion. According to hypothesis testing and multiple linear regression analysis, 1) the socio-economic conditions of parents At the same time, learning motivation was found to have a significant impact on economic achievement in learning. The acquisition of the values demonstrates 0.001b 0,05 and Fh = 7.503, 2) parents' socio economic circumstances have a significant influence on economic learning achievement. The acquisition of the values demonstrates Sig. 0,001 0.05 and th = 3.444 3) Motivation has a significant impact on economic achievement levels. The acquisition of the values demonstrates Sig.0.185 0.05 and Fh = 1.340.